Governing technology for sustainability - Murphy, Joseph (Earthscan, 2006)
In a world of growing complexity and dwindling resources, the relationship between technology and sustainability is a pressing issue of concern at the highest levels. This book improves our understanding by examining the ways that people, technology and governance shape each other with implications for sustainability. It is the first book to link technology studies and governance research to this problem. Contributions from leading environmental social scientists are included, with each chapter reporting on new research and tackling complex, but vital issues. Drawing on examples such as wave and tidal power, wind power, micro-generation, community waste recycling and eco-housing, the book provides powerful new insights into the governance of technology for sustainability. A detailed introduction and conclusion discuss existing research directions and identify the contribution that the book makes in advancing our understanding of the people-technology-governance nexus and its implications for sustainability. This is essential reading for all those in academia, government and industry working at the critical interface between how we develop, deploy and govern technology in the pursuit of sustainability.